METODE VECTOR AUTOREGRESSIVE (VAR) DALAM PERAMALAN JUMLAH WISATAWAN MANCANEGARA KE BALI - RANANGGA, TJOK GDE SAHITYAHUTTI; SUMARJAYA, I WAYAN; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika; Vol 7 No 2 (2018)DO - 10.24843/MTK.2018.v07.i02.p198, 2018)
The purposes of this research were to model and to forecast the number of foreign tourists (Australia, China, and Japan) arrival to Bali using vector autoregressive (VAR) method. The estimated of VAR model obtained to forecast the number of foreign tourists to Bali is the sixth order VAR (VAR(6)).We used multivariate least square method to estimate the VAR(6)’s parameters. The mean absolute percentage error (MAPE) in this model were as follows 6.8% in predicting the number of Australian tourists, 15.9% in predicting the number of Chinese tourists, and 9% in predicting the number of Japanese tourists. The prediction of Australian, Chinese, and Japanese tourists arrival to Bali for July 2017 to December 2017 tended  to experience up and downs that were not too high compared to the previous months.